International regulations and financial inclusion: Between dead-end and renouncement - Christophe Angely (Fondation pour les études et recherches sur le développement international (FERDI), 2023)
Banking services for individuals, businesses and even sovereign states have existed in various forms for thousands of years (from Sumerian times in Mesopotamia, 24 centuries BC1). To achieve this, financial institutions have had to rely on risk measurement tools which, for a very long time, were based on subjective analyses carried out by bankers with access to privileged information. This data on the characteristics of their client, often a borrower, were based on reputation, leverage2 , volatility of profits for the company and, most often, the existence of collateral in the event of default. This highly selective approach was certainly at the origin of the old popular saying, "you only lend to the rich and powerful. As surprising as it may seem, a more objective attitude towards risk, particularly credit risk, is a recent development. From the Industrial Revolution in the beginning of the 19th century up until the Great Crash of 1929 the financial system experienced a steady growth. After the 1929 crash, governments adopted global regulatory measures, such as the Glass- Steagall Act1 in the United States, to better com- bat or control the systemic risks associated with the speculative activities of institutions. From the time of the Great Depression onwards, the banking environment has become increasingly regulated at national, regional, and now global levels.
Keywords: 330; Banks